2017
DOI: 10.1021/acsomega.7b00162
|View full text |Cite
|
Sign up to set email alerts
|

Making a Supertough Flame-Retardant Polylactide Composite through Reactive Blending with Ethylene-Acrylic Ester-Glycidyl Methacrylate Terpolymer and Addition of Aluminum Hypophosphite

Abstract: Biocompatible and biodegradable polylactide (PLA) composites with supertough mechanical property and sufficient flame retardancy were fabricated by employing a facile approach involving reactive blending of PLA and ethylene-acrylic ester-glycidyl methacrylate terpolymer (EGMA), with the addition of aluminum hypophosphite (AHP) as an effective flame retardant. In consideration of the balance between mechanical property and flame retardancy, the optimal formula was taking a PLA/EGMA 80/20 blend (supertough STPLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The EE and EBG polymers have similar monomeric structures (ethylene chains); thus, their chemical affinity is higher than PLA–EBG. Li et al . reported that the T 5% temperature of PLA shifted from 351 to 360 °C after incorporating 20% ethylene–acrylic ester–glycidyl methacrylate (GMA) terpolymer in PLA.…”
Section: Resultsmentioning
confidence: 99%
“…The EE and EBG polymers have similar monomeric structures (ethylene chains); thus, their chemical affinity is higher than PLA–EBG. Li et al . reported that the T 5% temperature of PLA shifted from 351 to 360 °C after incorporating 20% ethylene–acrylic ester–glycidyl methacrylate (GMA) terpolymer in PLA.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to pure mycelium, the fire reaction properties of composites made from mycelium and wheat grain were measured experimentally using a cone calorimeter at an incident heat flux of 50 kW/m 2 , with temperatures ranging from 600 to 700 °C 38 40 . The composites were grown for 6, 12 and 18 d to ascertain the differences, if any, in their fire reaction properties associated with growth time.…”
Section: Combustion Properties Of Mycelium Compositesmentioning
confidence: 99%
“…Recently, mechanically tough FR PLA was reported by reactive blending of PLA with ethylene-acrylic ester-glycidyl methacrylate terpolymer (EGMA), with the addition of 20 wt % aluminum hypophosphite (AHP) as an effective flame retardant [43]. The matrix achieved a V-0 rating with an LOI of 26.6% and an appreciable reduction in peak heat release with an increase in the elongation at break by 22%.…”
Section: Current Trends In Flame-retardant Plamentioning
confidence: 99%